How to Understand School Refusal - Havik, Trude; Ingul, Jo Magne (Frontiers in Education, 2021)
Attending school is usually seen as a precondition for academic, social, and emotional learning. However, school absenteeism is a problem in many countries and covers different types of authorized or unauthorized absences and a myriad of reasons. An authorized absence is when there is a satisfactory explanation for the youth’s absence, while unauthorized absence is usually understood as school attendance problems. The main aim of this article is first to investigate define, describe, and discuss school refusal and how school refusal differs from other concepts of school attendance problems, and secondly to understand school refusal by using different theoretical perspectives. The article outlines this aim based upon previously international research in the field, and use the systemic integrated cognitive approach and school alienation theories to explain how school refusal might emerge and develop. The literature indicates that school attendance problems involve many types, concepts, definitions, and reasons. The most frequently used concepts are school refusal behavior, truancy, school refusal, and school withdrawal. The article argues for a common understanding of these concepts among all stakeholders. We suggest a narrow definition of school refusal to enhance clarity and agreement and propose that the systemic integrated cognitive approach and school alienation theory are relevant to understand school refusal. A common understanding among all stakeholders is of importance to identify and intervene in specific types of school attendance problems. By using a systemic integrated cognitive approach and school alienation theory, identification and interventions can be targeted at an early stage of the development process of school refusal.